Authority inspectiva and the public audit: Historic glance within the administrative environmental right cuban - Antúnez Sánchez, Alcides; Ramírez Sánchez, Amed (Derecho Público Iberoamericano, 2016)
The article accomplishes an exam on the work of the Regional Government Bodies, today these are acquiring a new dimension like Alert State, as from the tradicionalidad of the juridical classical doctrine that divided them into policeman’s activity, of fomentation and of public utility. It is a fact than The Environmental right gets perfect in last decades, but his application keeps on having not made suitable results, necesitándose of a bigger control through the show inspector the one that comes to an end with the execution of the public audit in the forms of step, in pursuit of conforming friendly companies with the environment to attain the sustainable development and to transform the present-day scene. [...]